EVOLUTION AND DIVERSIFICATION OF MUSEUM FUNCTIONS: A REFLECTION OF MARKET DEMAND IN PENANG, MALAYSIA - Rahman, Suraiyati; Velayuthan, Sathish Kumar (PLANNING MALAYSIA, 2020)
Changes in human values and technological advancements have led to the reinvention of museum interpretation. Studies have shown that the transformation of museums’ functions and emerging typology of museums occur globally. Initially, museums’ function was to educate society and preserve artefacts for public access, but nowadays, museums have expanded their functions and have become market driven. The increasing number of museum establishments in George Town, Penang has mixed impacts to the curatorship and interpretation of museums. The strategic location of George Town, Penang, its branding as a World Heritage Site, cultural heritage attractions, and local values have gained popularity as a touristic destination. Museums and galleries are the top attractions reviewed by users in TripAdvisor. This article investigates the transformation of functions and typology of museums on the basis of the top 20 museums in Penang listed in TripAdvisor. Content analysis from the secondary data was conducted to establish the pattern and trends of museums’ diversification in Penang. Findings revealed that the diversification of museums in Penang has expanded from histories such as natural, science, human, and art to history and art, technology, and specialty. Considering that George Town has been nominated as a World Heritage Site, museums have become consumer oriented, and private ownership and collaborative partnership have grown drastically. This study contributes by showing that the diversification of museums’ function enhances creativity to meet future needs.